Sudden cardiac death: mandatory exclusion of athletes at risk is a step too far. Issue 5 (28th October 2011) - Anderson, Lynley; Exeter, Dan; Bowyer, Lynne
Abstract : Sudden cardiac death (SCD) in young athletes is a distressing event and it is not surprising that some physicians working with sports people are proposing that preventive action should be taken. There is a push for a system similar to that established in some countries, which involves screening and mandatory exclusion of those at risk. We argue that while screening can provide useful information to at-risk athletes making decisions about their future athletic careers, mandatory exclusion of athletes is paternalistic and such decisions are not rightfully within the domain of medicine.